Pyramiding of High Grain Weight With Stripe Rust and Leaf Rust Resistance in Elite Indian Wheat Cultivar Using a Combination of Marker Assisted and Phenotypic Selection - Kaur, Satinder; Kaur, Jaspreet; Mavi, G. S.; Dhillon, Guriqbal Singh; Sharma, Achla; Singh, Rohtas; Devi, Urmila; Chhuneja, Parveen (Frontiers in Genetics, 2020)
Wheat (Triticum aestivum L.) is an important cereal crop of India, and worldwide and yield improvement programmes suffer a strong impediment from ever evolving rust pathogens. Improving the durability of rust resistance is always a priority for better yields. In the present study high thousand grain weight (TGW) has been transferred into two elite Indian wheat cultivar PBW343 and PBW550 from a high TGW selection, Rye selection 111, selected from local germplasm. In PBW343 background, an increase in TGW of 8.82g - 10.27g was observed while PBW 550 background showed a rise of TGW of 5.27g - 7.6g through conventional backcross breeding and phenotypic selections. Resistance to leaf rust and stripe rust have been incorporated in the high TGW version of PBW550 (called HGW550) through marker assisted pyramiding of Yr15 and linked Lr57-Yr40 genes. Improved versions of PBW550 with increased TGW ranging from 45.0g - 46.2g and three stacked genes for stripe and leaf rust resistance were generated, which is a valuable resource for breeding elite cultivars.